The effects of different exercise loads in plyometric resistance training on respiratory and hormonal levels in female volleyball players - Kavuran, K.; Tizar, E.; Oral, D.; Erdogan, R.; Çelikel, B. E.; Ceylan, T.; Sezer, S. Y.; Karatas, B. (Frontiers in Physiology, 2025)
Background: The present study set out to ascertain the effects of combined exercises, consisting of resistance training and plyometric exercises at varying degrees of intensity, on biochemical and respiratory parameters in female volleyball players.